Early sedation use in critically ill mechanically ventilated patients: when less is really more - Lee, Christie M (Crit Care, 2014)
Over the last 10 years, there has been an explosion of literature surrounding sedation management for critically ill patients. The clinical target has moved away from an unconscious and immobile patient toward a goal of light or no sedation and early mobility. The move away from terms such as ‘sedation’ toward more patient-centered and symptom-based control of pain, anxiety, and agitation makes the management of critically ill patients more individualized and dynamic. Over-sedation has been associated with negative ICU outcomes, including longer durations of mechanical ventilation and lengths of stay, but few studies have been able to associate deep sedation with increased mortality.